Investigating the Use of Digital Consumption for Responsible Ride-Hailing Services in Indonesia Younger Generations - Asfarian, Auzi; Sukmasetya, Pristi; Ramadhan, Dean Apriana; Athoetan, Salma; Hasbi Hutauruk1, Dzakiyyah; Firdaus Anavyanto, Arazka; Annisa; Noris Mohd Norowi (Universitas Muhammadiyah Surakarta, 2024)
This study thoroughly examined responsible consumption implemented in Indonesia's ride-hailing services. We employed a mixed-methods approach that integrated quantitative data from the Socially Responsible Purchase and Disposal (SRPD) questionnaire with qualitative insights derived from think-aloud protocols and interviews. Our objective was to examine data and identify discrepancies between attitudes and behaviors among young individuals aged 18-29 to provide directions for future research. The results of our study uncovered substantial disparities between the attitudes that participants expressed and their subsequent actions. Although individuals acknowledge the importance of responsible consumption, the testing shows that they rarely use features related to responsible consumption, such as carbon funds, electric vehicle options, and tipping. Several key factors they stated are increased cost, lack of awareness of the features of responsible consumption, lack of perceived trust, and transparency of funds. Based on the interview, the personal connection between participants and ride-hailing drivers encourages them to tip more. Our research highlights the critical gap between attitudes and actions in responsible ride-hailing services in Indonesia's younger generation, which can be solved by implementing proper digital nudges. This research emphasizes the importance of further research to bridge this gap and encourage more accountable digital consumption.